THE IMPACT OF REKLAMATIOH AHD CEMICAL FERTILIZERS ON CORH YIELD AND PHYSIKO-CHEMIKAL PROPERTIES OF SOIL - Яворов, В. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
It was observed the influence of limestone and dolomite as well as its backdrop of fertilizers on the physic-chemical properties of gray podzolized medium loamy soil on the growth and corn yield. The researches had established that the introduction of limestone flour 3 t ha increased the pH of water. from 5,3 to 6.0; pH Sol. from 4,6 to 5,4. The dolomite weaker was showed weaker neutralizing ability. The acidity in this embodiment had dropped by 0,5 pH water. And 0,4 pH Sol. Adding fertilizer N 35 35 P35 K in background chemical meliorants slightly reduced the positive effect of the latter on the physical and chemical soil properties. The best plant growth and plants’ development and corn yield was obtained on the version, limestone flour + N35K35P35. The indicators according were totaled 206, 5 sm and 47,3 ts/ha. Compared to control corn yield had increased to 12,6 ts/ha or 36,3%.